Building Patent Portfolios to Facilitate Cross-Licensing Agreements: Implications for Merger Efficiency Analysis - Dorsey, Elyse (Science and Technology Law Review, 2013)
The intersection of antitrust and patent law has increased in scope and importance over the past several decades. One important issue at this cross-section is the patent holdup problem, which arises when one party makes relationship-specific investments ex ante that incentivizes the other party to engage in opportunistic behavior ex post. Firms facing the potential for holdup can be expected to make investments aimed at minimizing this potential. Numerous methods of solving the holdup problem exist, including using ex ante auctions to identify and alleviate holdup problems, as well as patent reform. Merger is another important, but thus far little-discussed, method by which firms can attempt to solve potential holdup problems. Merger internalizes the externalities that allow for patent holdup. By merging, two firms with relatively undeveloped patent portfolios may gain meaningfully increased bargaining power in licensing negotiations, which they may use to facilitate cross-licensing agreements—thereby decreasing transactions costs and reducing the risk of opportunistism. For purposes of antitrust analysis, courts, agencies, and economists have long recognized that significant efficiencies often derive from cross licensing, including increases in output arising from the diminished marginal costs of production. As the Google-Motorola acquisition exemplifies, merger may provide an important alternative solution to holdup problems, despite being largely overlooked in the contemporary patent holdup debate. This acquisition potentially provides Google with leverage and ownership rights to protect the entire Android ecosystem that cannot be accomplished by alternative contractual structures. Such a merger—which increases output that cannot be achieved by alternative structures—appears to satisfy the basic definition of a merger efficiency. Whether these benefits—which presumably would increase output—are cognizable efficiencies in merger analysis is thus an important question.